An Improved Variable Sample Size And Sampling Interval S Control Chart - See, May Yen (2018)
The standard deviation chart or S chart is used to monitor the process standard deviation. In this thesis, some of the features of the S chart are altered to increase the chart’s sensitivity towards small and moderate shifts in the process standard deviation. This new chart for monitoring the process standard deviation is known as the improved variable sample size and sampling interval ( t VSSI ) S chart.The design and construction of the t VSSI S chart is based on the idea of the improved variable sample size and sampling interval ( t VSSI ) X chart proposed by Noorossana et al. in 2016. The t VSSI X chart improves the efficiency of the X-type charts in detecting small and moderate shifts in the process mean.